2017
DOI: 10.1038/cddis.2016.455
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin represses mouse 3T3-L1 cell adipogenic differentiation via inhibiting miR-17-5p and stimulating the Wnt signalling pathway effector Tcf7l2

Abstract: Understanding mechanisms underlying adipogenic differentiation may lead to the discovery of novel therapeutic targets for obesity. Wnt signalling pathway activation leads to repressed adipogenic differentiation while certain microRNAs may regulate pre-adipocyte proliferation and differentiation. We show here that in mouse white adipose tissue, miR-17-5p level is elevated after high fat diet consumption. miR-17-5p upregulates adipogenic differentiation, as its over-expression increased while its inhibition repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 48 publications
2
71
0
Order By: Relevance
“…Curcumin was reported to modulate some miRNAs that are dysregulated in diabetes. In a study conducted by Tian et al, miR-17-5p was proven to stimulate adipogenic differentiation of mouse 3T3-L1 cells [89]. This gene encodes a key Wnt signaling pathway effector, and its human homologue transcription factor 7 like-2 (TCF7L2) is a highly diabetes risk gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin was reported to modulate some miRNAs that are dysregulated in diabetes. In a study conducted by Tian et al, miR-17-5p was proven to stimulate adipogenic differentiation of mouse 3T3-L1 cells [89]. This gene encodes a key Wnt signaling pathway effector, and its human homologue transcription factor 7 like-2 (TCF7L2) is a highly diabetes risk gene.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also reported an elevation of miR-17-5p expression in mouse epididymal fat tissue in response to high fat diet. The authors suggested that miR-17-5p is among the central switches of adipogenic differentiation, activating adipogenesis via repressing the Wnt signaling pathway effector Tcf7l2, and its own expression is nutritionally regulated by curcumin [89].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Polyphenols provide a wide range of anti-carcinogenic health benefits. [15][16][17][18][19][20][21][22] However, polyphenol absorption is reportedly very low.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, curcumin has been shown to repress hepatic gluconeogenic gene expression via AMPK activation [32] and to activate the canonical Wnt signaling cascade in white adipose tissue to repress adipogenesis [33][34][35] . These effects, in the long run, may generate indirect effects on insulin sensitivity.…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%